Efficacy of linaclotide in combination with polyethylene glycol for bowel preparation in Chinese patients undergoing colonoscopy polypectomy: protocol for a randomised controlled trial - Jing Xu; Ping-ping Chen; Dong Chen; Hui-Ying Zhao; Xiao-Feng Cai; Xiao-Bin Wang; Chao-Xu Liu (BMJ Open)
Background Adequate bowel preparation is essential for successful colonoscopy and polypectomy procedures. However, a significant proportion of patients still exhibit suboptimal bowel preparation, ranging from 18% to 35%. The effectiveness of bowel preparation agents can be hampered by volume and taste, adversely affecting patient compliance and tolerance. Therefore, exploring strategies to minimise laxative volume and improve patient tolerance and adherence is imperative to ensure optimal bowel preparation quality.Methods and analysis This study is a two-arm, single-blinded, parallel-group randomised controlled trial designed to compare the efficacy of 2 L polyethylene glycol (PEG) combined with linaclotide with 4 L PEG in bowel cleansing. A total of 422 participants will be randomly assigned in a 1:1 ratio to either the intervention group (2 L PEG combined with 580 µg linaclotide) or the control group (4 L PEG). The primary outcome measure is bowel cleansing efficacy, which is assessed using the Boston Bowel Preparation Scale. Secondary outcomes include evaluating the tolerability and safety of the bowel preparation regimens, bowel diary assessments, postpolypectomy complications (such as bleeding and perforation) and the size and number of removed polyps.Ethics and dissemination The study has received approval from the Clinical Research Ethics Committee of The First Affiliated Hospital, Zhejiang University School of Medicine. The findings of this trial will serve as a valuable resource for clinicians and patients undergoing colonoscopy polypectomy by guiding the selection of appropriate bowel preparation regimens. Study findings will be disseminated to participants, presented at professional society meetings, and published in peer-reviewed journals. This trial was registered on the Chinese Clinical Trial Registry with registration number ChiCTR2300075410